1996
DOI: 10.1042/bj3170667
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling effect of polyunsaturated fatty acid deficiency in isolated rat hepatocytes:effect on glycerol metabolism

Abstract: The effects of a 4-week deficiency in polyunsaturated fatty acids (PUFA) in isolated rat hepatocytes have been investigated for oxidative phosphorylation and fatty acid, dihydroxyacetone (DHA) or glycerol metabolism. Oxygen uptake was significantly increased (by 20%) with or without fatty acid addition (octanoate or oleate) in the PUFA-deficient group compared with controls. The effect persisted after oligomycin addition but not after that of potassium cyanide, leading to the conclusion that, in these intact c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…In other words, the number of ATP moles produced per O 2 consumed (energy yield of O 2 ) could be lower in n-3-depleted versus control animals, irrespective of the substrate used, as a result of wasting processes. Studies in both isolated mitochondria and intact cells have shown that n-3 PUFA deficiency causes an increase in proton permeability of the inner mitochondrial membrane, similar to that caused by the classical protonophore 2,4-dinitrophenol (18). Thirdly, the n-3 PUFA deficient diet could alter energy transfer from mitochondria to sites of energy utilization through an effect on phosphotransfer kinases (19).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the number of ATP moles produced per O 2 consumed (energy yield of O 2 ) could be lower in n-3-depleted versus control animals, irrespective of the substrate used, as a result of wasting processes. Studies in both isolated mitochondria and intact cells have shown that n-3 PUFA deficiency causes an increase in proton permeability of the inner mitochondrial membrane, similar to that caused by the classical protonophore 2,4-dinitrophenol (18). Thirdly, the n-3 PUFA deficient diet could alter energy transfer from mitochondria to sites of energy utilization through an effect on phosphotransfer kinases (19).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins in the perifusate were denatured by heating the samples (80°C for 10 min) before centrifugation (36). Glucose, lactate, and pyruvate were measured in the perifusate and DHAP; glucose 6-phosphate; fructose 6-phosphate; 3-phosphoglycerate; and PEP were measured in the cellular fraction as described previously (31)(32)(33)(34)(35). The net fluxes (micromoles/min/g of dry cells) of gluconeogenesis (J glucose ), glycolysis (J lactate ϩ pyruvate ), and DHA metabolism (J DHA ), were calculated from the total cell content of the perifusion chamber, the perifusate flow rate, and the concentration of glucose, lactate, and pyruvate in the perifusate.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes were perifused at 37°C at a flow rate of 5 ml⅐min Ϫ1 with Krebs bicarbonate buffer (pH 7.4) continuously saturated with O 2 /CO 2 (19:1) and containing calcium (1.3 mM) (32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocytes were isolated by the method of Berry and Friend (16) (19,20). To study the metabolic effect of glucagon, perifused liver cells were titrated with DHA in the presence or absence of glucagon (10 Ϫ7 M).…”
Section: Methodsmentioning
confidence: 99%